Willingness to pay for the recovery and conservation of urban green areas for public use in the city of Juliaca, Peru - Mamani, Julio Cesar Quispe; Gallardo, Nelly Jacqueline Ulloa; Mamani, Marcial Guevara; Vilca, Alberto Catachura; Guizada, Cesar Elías Roque; Mamani, Freddy Abel Rivera (The journal of contemporary issues in business and government, 2021)
The objective of the research was to determine the willingness to pay for the recovery and conservation of existing urban green areas for public use in the city of Juliaca, as an approximation of their economic value. The methodology used was the contingent valuation method (CVM), through the application of 383 surveys to people who visit green areas, these data were analyzed using the STATA and SPSS programs. For the estimation, the cloglog regression model was used, where the results obtained show that the main variables that influence the willingness to pay for recovery and conservation are their level of monthly family income, education, the proximity of the green area to their home. , the frequency with which you visit the green area and the perception of the state of the green area. 80% of citizens are willing to pay for the recovery and conservation of existing green areas, where the average willingness to pay is S /. 5.16 soles. Finally, it is to be expected that the results obtained may be a useful and necessary source of information on urban planning, environmental education and environmental culture.